Evaluation of the Effects of Gender Differences on Personality Traits and Life Satisfaction (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: This was a causal-comparative study aimed to comparatively evaluate the personality characteristics and life satisfaction among the individuals resident of district 6 Tehran, Iran. Method: The research population consisted of 661 individuals (â‰¥20-year-old; 49.5% male and 51.5% female) selected through stratified random sampling method in five different age groups. The data were collected using researcher-made demographic questionnaire, NEO Five-Factor Inventory short form, and satisfaction with life scale (Diener et al.). The data were analyzed with independent t-test. Result and Discussion: Results of independent t-test indicated that the 20-30 years old women received significantly higher scores in neuroticism and agreeableness features than men and between men and women were not observed a significant difference in extroversion, openness to experience, and conscientiousness in different age groups. In addition, the life satisfaction score of the 20-30 years old age group of women was significantly higher than men, other personality characteristics in relation to life satisfaction were not significantly different. Conclusion: The status of neuroticism, agreeableness, and life satisfaction in 20-30 years old women were discussed. Further conducting studies on the psychological characters of young age groups of women is necessary.